Research on High Speed Phased Array Ultrasonic Inspection System - Zhang, Yu; Gao, Xiao-Rong; Peng, Chao-Yong; Wang, Zhen; LI, Xi (2017 Far East NDT New Technology & Application Forum (FENDT), 2017)
As the main part of railway, rail's quality has a direct influence on rail transportation safety. At present, conventional ultrasonic technology is commonly used in rail inspection system, however, it exists some shortages such as slow inspection speed, low rail coverage, bad adaption to different rail type and low detection rate. This paper introduces a high-speed rail inspection system, it combines fast ultrasonic phased array technology with high-speed processing algorithm such as expert diagnose algorithm, to improve inspection speed to 100km/h, coverage area of rail and defect detection rate, and can automatically recognize defects, which meet the new requirement of high -speed, high efficiency and high intelligence.